Fundamental parameter accuracy of DA and DB white dwarfs in Gaia Data Release 2. Issue 4 (10th November 2018) - Tremblay, P-E; Cukanovaite, E; Gentile Fusillo, N P; Cunningham, T; Hollands, M A
ABSTRACT: We report on a comparison of spectroscopic analyses for hydrogen (DA) and helium atmosphere (DB) white dwarfs with Gaia Data Release 2 (DR2) parallaxes and photometry. We assume a reddening law and a mass–radius relation to connect the effective temperatures ( T eff ) and surface gravities (log g ) to masses and radii. This allows the comparison of two largely independent sets of fundamental parameters for 7039 DA and 521 DB stars with high-quality observations. This subset of the Gaia white dwarf sample is large enough to detect systematic trends in the derived parameters. We find that spectroscopic and photometric parameters generally agree within uncertainties when the expectation of a single star is verified. Gaia allows the identification of a small systematic offset in the temperature scale between the two techniques, as well as confirming a small residual high-mass bump in the DA mass distribution around 11 000–13 000 K. This assessment of the accuracy of white dwarf fundamental parameters derived from Gaia is a first step in understanding systematic effects in related astrophysical applications such as the derivation of the local stellar formation history, initial-to-final mass relation, and statistics of evolved planetary systems.